Participation in Community-Originated Interventions is Associated with Positive Changes in Weight Status and Health Behaviors in Youth - Whetstone, Lauren; Kolasa, Kathryn M.; Collier, David N. (My University, 2012)
Purpose. To assess changes in children’s health behaviors and weight status after participation in community-originated interventions. Design. Prospective cohort study following body mass index (BMI) z-score trajectory over time. Setting. Schools and community settings in 19 locations in North Carolina. Subjects. A total of 1144 children, with an average age of 9.5 years, participating in community-originated physical activity and nutrition interventions, such as active recess and healthy cafeteria offerings, and environment and policy changes designed to prevent and reduce the prevalence of childhood obesity. Retention from baseline to final collection was 54%. Measures. Self-reported physical activity and eating behaviors; measured height and weight were collected at baseline and after interventions (average of 20 months). Z-score was compared with expected growth without intervention. Analysis. Descriptive statistics, χ2 tests and t-tests, and analysis of variance to assess changes in health behaviors and weight status. Results. More than 11% of children improved their weight status, and 86% of children who began at a healthy weight remained there. The average BMI for children who were overweight at enrollment was significantly lower after intervention (1.1 kg/m2 lower for boys and 0.88 kg/m2 lower for girls). Overweight and obese children who made improvements in key health behaviors showed greater decreases in BMI z-score than those who did not improve those behaviors (increased fruit [−.2207 vs. −.0793] and vegetable [−.2215 vs. −.0855] intake, and drinking less soda [−.1985 vs. −.0912]). There were no significant increases in physical activity, and changes in physical activity were not related to decreases in BMI z-score in this study. Conclusion. Community-originated interventions to raise awareness about food choices and to change policies and environments may improve BMI z-scores.
Keywords: Childhood obesity; Community-based interventions; Dietary change; Physical activity